Why Was There So Little Government Reaction to Gunpowder Plot? - Okines, A. W. R. E. (The journal of ecclesiastical history, 2004)
This article rejects the approach that treats the Gunpowder Plot as a discrete historical episode. The plot is better understood when examined in parallel with the period after November 1605; the surprising leniency shown by the Jacobean government towards English Catholics destroys the motives upon which conspiracy theories are based. This article demonstrates that Robert Cecil, earl of Salisbury, supported King James's toleration since both wished to preserve domestic stability and peace with Spain. The assassination of King Henri IV of France in 1610 did more to jeopardise toleration than did the Gunpowder Plot, despite the latter's profound impact on the English popular consciousness.